The Long and the Short of PTEN in the Regulation of Mitophagy - Wang, Liming; Lu, Guang; Shen, Han-Ming (Frontiers in Cell and Developmental Biology, 2020)
Mitophagy is a key mitochondrial quality control mechanism for effective and selective elimination of damaged mitochondria through the autophagy-lysosome machinery. Defective mitophagy is associated with pathogenesis of important human diseases including neurodegenerative diseases, heart failure, innate immunity and cancer. In the past two decades, the mechanistic studies of mitophagy have made many breakthroughs with the discoveries of phosphatase and tensin homolog (PTEN)-induced kinase protein 1 (PINK1) ubiquitin (Ub)-driven pathway and BCL2/adenovirus E1B 19 kDa protein-interacting proteins 3 (BNIP3)/NIX or FUN14 domain containing 1 (FUNDC1) receptor-mediated pathways. Recently, several isoforms of dual phosphatase PTEN, such as PTEN-Long (PTEN-L), have been identified, and some of them are implicated in the mitophagy process via their protein phosphatase activity. In this review, we aim to discuss the regulatory roles of PTEN isoforms in mitophagy. These discoveries may provide new opportunities for development of novel therapeutic strategies for mitophagy-related diseases such as neurodegenerative disorders via targeting PTEN isoforms and mitophagy.